Geoheritage Conservation in Ethiopia: The Case of the Simien Mountains - Asrat, Asfawossen; Metasebia, Demissie; Aberra, Mogessie (Wydział Nauk Geograficznych i Geologicznych UAM, 2012)
Ethiopia constitutes one of the most significant environmental and cultural reserves on Earth. Ethio¬pia’s natural and cultural tourist attractions are mostly associated with geological features: the active Ethiopian and Afar rifts as well as the Simien and Bale massifs are few examples. Ethiopia’s cultural history, religious ma¬nifestations and civilization, like the rock-hewn churches of Lalibela and the stelae of Axum, are also imprinted in rock. Geomorphological and geological features, notably the isolation of the north-western highlands from the external world by the harsh Afar depression close to the sea, determined the route of Ethiopian history. Though tourism has been identified as a major sustainable development sector, systematic geoheritage evaluation and conservation strategies are lacking in the country. In this paper the Simien Mountains are presented as major geoheritages which should be prioritized for geoconservation in order to develop sustainable tourism (geotourism) in the area.
Keywords: geoheritage; geotourism; geoconservation; sustainable development; Simien Mountains; Ethiopia